Cáncer, chabolas y castración: el Madrid de la posguerra en Tiempo de Silencio, de Luis Martín-Santos. - Muñoz, Marianela (2012)
Given three textual elements: mice cancer, life in shanties and castration, a metonymy of the Spanish postwar is constructed in the novel Tiempo de Silencio. The symbolic values of these images assemble a city that determines the failure and the final exclusion of the main character, thus criticizing the environment during Franco's dictatorship.